The Accuracy of Fatal Officer-Involved Shooting Data: A Response to “The Limitations of Government Databases for Analyzing Fatal Officer-Involved Shootings in the United States”: - Beck, Charlie (Criminal justice policy review, 2019)
This essay responds to an article by Williams, Bowman, and Jung concerning fatal officer-involved shootings (OISs) and Federal and state databases that appeared in the Criminal Justice Policy Review. We write in response to the article because of our concern about the claim that data from individual police agencies, including the Los Angeles Police Department (LAPD), were classified as “missing” or were not reported to the Federal Bureau of Investigation (FBI) and in our case, the California Department of Justice. This essay provides a much-needed context for fatal OISs. The essay (a) defines use of force and explains the level of oversight for OISs, (b) provides a brief analysis of LAPD OISs from 2006 to 2015, (c) discusses the “missing or nonreported” LAPD cases, and (d) presents our conclusions about fatal OIS data.